2002
DOI: 10.1038/nature00908
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative demethylation by Escherichia coli AlkB directly reverts DNA base damage

Abstract: Methylating agents generate cytotoxic and mutagenic DNA damage. Cells use 3-methyladenine-DNA glycosylases to excise some methylated bases from DNA, and suicidal O(6)-methylguanine-DNA methyltransferases to transfer alkyl groups from other lesions onto a cysteine residue. Here we report that the highly conserved AlkB protein repairs DNA alkylation damage by means of an unprecedented mechanism. AlkB has no detectable nuclease, DNA glycosylase or methyltransferase activity; however, Escherichia coli alkB mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
630
1
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 721 publications
(659 citation statements)
references
References 25 publications
16
630
1
7
Order By: Relevance
“…For example, it is exciting if some members have DNA modification activity, such as a DNA demethylase. As described above, bacterial AlkB protein, a 2-OG-Fe(II)-dependent dioxygenase, is involved in DNA repair by DNA demethylation (Falnes et al, 2002;Trewick et al, 2002), suggesting the possibility. Because DNA modification as well as histone modification are very important events for making epigenetic signatures, the possibility is very interesting.…”
Section: What Molecular Functions Do Each Jumonji Family Protein or Tmentioning
confidence: 86%
See 1 more Smart Citation
“…For example, it is exciting if some members have DNA modification activity, such as a DNA demethylase. As described above, bacterial AlkB protein, a 2-OG-Fe(II)-dependent dioxygenase, is involved in DNA repair by DNA demethylation (Falnes et al, 2002;Trewick et al, 2002), suggesting the possibility. Because DNA modification as well as histone modification are very important events for making epigenetic signatures, the possibility is very interesting.…”
Section: What Molecular Functions Do Each Jumonji Family Protein or Tmentioning
confidence: 86%
“…The structure of jmjC of HIF1AN/FIH (Elkins et al, 2003) and alignment of the aminoacid sequence of Epe1 and jumonji family proteins suggested that many jumonji family proteins have structures and enzymatic activities similar to those of HIF1AN/FIH. Escherichia coli AlkB family proteins, which remove methyl groups in DNA through oxidative demethylation (Falnes et al, 2002;Trewick et al, 2002), are also 2-OG-Fe (II)-dependent dioxygenases. The above hypothesis was proposed based on analogy of the mechanisms of demethylation by AlkB proteins.…”
Section: Functions Of Jumonji Family Proteins In Transcription and Chmentioning
confidence: 99%
“…However, a reversible tRNA modification process that could noticeably affect gene expression has yet to be shown. FTO and ALKBH5 are RNA demethylases that belong to the human AlkB family dioxygenases that utilize a nonheme iron(II) to catalyze biological oxidation (Falnes et al, 2002;Gerken et al, 2007;Loenarz and Schofield, 2008;Trewick et al, 2002). Almost all of the AlkB family members with known biological functions work on nucleic acid substrates (Fedeles et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They detected the formation of formaldehyde and showed that the AlkB protein utilizes a previously unknown oxidative demethylation pathway to repair 1-meA and 3-meC DNA damage ( Fig. 1(c)) [30,31]. Thus, in the ada operon both Ada and AlkB use the direct repair pathways to remove methylation DNA damage.…”
mentioning
confidence: 99%